Determination of rheological properties of some pekmez samples in Turkey - Yogurtcu, H.; Kamisli, F. (Elsevier Sci Ltd, 2006)
The rheological behaviors of pekmez samples (mulberry, grape, rosehip and harnup juice) were investigated. Viscosity was measured at 5, 10, 15, 20 and 30 degrees C using a rotational viscometer in the shear rate range of 0-93 s(-1). An emprical power-law model was used to describe the rheological behaviors of pekmez samples. Pekmez samples were found to exhibit non-Newtonian behaviors. An Arrhenius equation was used to determine the effect of temperature on viscosities of pekmez samples and thus Ea values of pekmez samples were calculated. The activation energies vary from 18.509 to 74.658 kJ/mol depending on the solid contents (39.44, 60.48, 67.08, 69.68, 71.98, 74.22, 75.4 and 75.46 degrees Brix). (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: pekmez; viscosity; power-law model; Arrhenius equation